Technology Assessment of Clean Coal Technologies for China : Volume 2. Environmental and Energy Efficiency Improvements for Non-power Uses of Coal - World Bank (Washington, DC, 2014)
Analysts expect China to continue improving the efficiency of energy production and use, thereby decoupling the traditional relationship between gross domestic product (GDP) and energy consumption. Environmentally acceptable economic growth is closely linked with further improvements in the overall efficiency of energy use. Both of these goals will require a continued increase in the use of coal to produce electricity, along with a more deliberate and rapid transition from direct coal combustion to the use of electricity and other cleaner coal-based fuel sources, especially for cooking, space heating, and industrial furnaces. The opportunity for environmental improvement in conjunction with economic growth lies in the wise adoption of clean coal technologies (CCT) for both the electric power and non-power sectors. This report presents CCT options for the power sector that can help China achieve these twin goals. The CCT options are: 1) air pollution controls for particulates, sulphur dioxide, and nitrous oxide; and 2) advanced electricity generation technologies--supercritical pulverized-coal boilers, atmospheric and pressurized fluidized-bed combustors, and integrated gasification combined cycle plants. Volume 1 of this report explains the project costing methodology and the electric power CCT options. Volume 2 summarizes the development and technology assessment of clean coal technologies for the non-power sector in China.